Analisis Peran Asuransi Syariah Dalam Mendukung Pertumbuhan Ekonomi Indonesia : Systematic Literatur Riview. - Anggini, Rizki; Soemitra, Andri; Qarni, Waizul (Gorontalo State University, 2026)
Sharia insurance in Indonesia is growing rapidly and plays an important role in the Islamic financial system and the national economy. This study aims to examine the role of sharia insurance in supporting Indonesia's economic growth from financial, social, and Islamic value perspectives. This study employs a Systematic Literature Review (SLR) method with 16 journal articles (2021-2025). The results show that sharia insurance contributes in three ways: as a risk protector stabilizing the micro-economy of households and MSMEs, as a collector and distributor of productive funds to the real sector and State Sukuk, and as a driver of financial inclusion and the achievement of SDGs. To optimize its contribution, strong governance, consistent regulations, spin-off of sharia business units, product innovation, integration with the real sector, and improved digital literacy are needed. Future research may examine linkages with MSMEs, the halal industry, and policy effectiveness.